2021
DOI: 10.3390/ani11102789
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of FATP1 on Adipocyte Differentiation in Qinchuan Beef Cattle

Abstract: FATP1 plays an important role in the regulation of fatty acid metabolism and lipid accumulation. In this study, we investigated the patterns of FATP1 expression in various tissues obtained from calf and adult Qinchuan cattle, and in differentiating adipocytes. Next, we investigated the effect of FATP1 expression on preadipocyte differentiation in Qinchuan cattle using overexpression and interference assays. We also identified the differentially expressed genes (DEGs) and pathways associated with FATP1 overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this study, through the transcriptomics and metabolomics analysis of SAT, VAT, and AAT, 11 candidate genes were identified to affect fat deposition via their involvement in fatty acid synthesis, metabolism and oxidation, pyruvate metabolism, and carbohydrate synthesis and digestion (Figure 12), including fatty acid synthesis genes (ACACA, SCD, and ELOVL6), fatty acid oxidation genes (EHHADH and CPT2), ketoacid metabolism genes (ACADSB and OCXT1), glycolytic genes (PCK1 and PCK2), fatty acid transporter genes FABP7, and CHPT1. Additionally, it was further confirmed that PPAR signaling pathway was a pivotal pathway associated with fat deposition [41,42]. sic gene expression [40].…”
Section: Discussionmentioning
confidence: 78%
“…In this study, through the transcriptomics and metabolomics analysis of SAT, VAT, and AAT, 11 candidate genes were identified to affect fat deposition via their involvement in fatty acid synthesis, metabolism and oxidation, pyruvate metabolism, and carbohydrate synthesis and digestion (Figure 12), including fatty acid synthesis genes (ACACA, SCD, and ELOVL6), fatty acid oxidation genes (EHHADH and CPT2), ketoacid metabolism genes (ACADSB and OCXT1), glycolytic genes (PCK1 and PCK2), fatty acid transporter genes FABP7, and CHPT1. Additionally, it was further confirmed that PPAR signaling pathway was a pivotal pathway associated with fat deposition [41,42]. sic gene expression [40].…”
Section: Discussionmentioning
confidence: 78%
“…In addition to stimulating lipogenesis, FATP1 ( SLC27A1 ) participates in the differentiation of pre-adipocytes regulated by PPAR [ 86 , 92 ]. During adipogenesis, FATP1 increases the release of triglycerides into plasma and promotes the uptake of fatty acids by pre-adipocytes [ 93 ]. Once inside the cells, fatty acids bind to the ligand-binding domain that modifies the structure of PPAR, forming a heterodimer with the retinoid X receptor (RXR) [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stimulating lipogenesis, FATP1 (SLC27A1) participates in the differentiation of pre-adipocytes regulated by PPAR [90,96]. During adipogenesis, FATP1 increases the release of triglycerides into plasma and promotes the uptake of fatty acids by pre-adipocytes [97]. Once inside the cells, fatty acids bind to the ligand-binding domain that modifies the structure of PPAR, forming a heterodimer with the retinoid X receptor (RXR) [55].…”
Section: Differentially Expressed Genes and Alterations In Biological...mentioning
confidence: 99%